2011
DOI: 10.4314/as.v10i1.68718
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Climate Change in the Derived Savannah Niche of Nsukka, South-Eastern Nigeria

Abstract: To track changes in our climate over the past 40 years, three important weather elements namely; temperature, rainfall and relative humidity were analyzed. The results obtained revealed that there is a trend towards warmer temperatures, fluctuating rainfall distribution pattern and reduced relative humidly in the derived savanna ecological belt. The period, 2005-2010, represents the six warmest years in the past four decades in the derived savanna ecology. The bi-modal rainfall pattern is still in place but wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 1 publication
1
24
0
4
Order By: Relevance
“…Il en est de même pour la prolifération des insectes qui a été signalé comme impact des changements climatiques sur le sésame (Luka et Yahaya, 2012). La pourriture des tubercules d'igname dans les buttes sous l'effet de la chaleur ou d'un excès d'eau a été un impact négatif important signalé par les producteurs et qui se justifie car la température du sol affecte le développement des plantes plus que tout autre facteur et les précipitations excessives rendent de nombreuses cultures vulnérables à l'engorgement (Uguru et al, 2011). La dégradation et la baisse de la fertilité des sols contribuent aussi énormément à la chute de la production (Luka et Yahaya, 2012).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Il en est de même pour la prolifération des insectes qui a été signalé comme impact des changements climatiques sur le sésame (Luka et Yahaya, 2012). La pourriture des tubercules d'igname dans les buttes sous l'effet de la chaleur ou d'un excès d'eau a été un impact négatif important signalé par les producteurs et qui se justifie car la température du sol affecte le développement des plantes plus que tout autre facteur et les précipitations excessives rendent de nombreuses cultures vulnérables à l'engorgement (Uguru et al, 2011). La dégradation et la baisse de la fertilité des sols contribuent aussi énormément à la chute de la production (Luka et Yahaya, 2012).…”
Section: Discussionunclassified
“…Les données sont collectées sur la base de questionnaires selon Nyanga et al (2011 Uguru et al (2011). L'identification des années ayant eu des conditions climatiques extrêmes a été faite en calculant le pourcentage du déficit ou de l'excédent des précipitations par rapport à la moyenne selon Yabi et Afouda (2012).…”
Section: Materiel Et Methodes Présentation De La Zone D'étudeunclassified
“…Nsukka (6°51' E, 7°29' N; 475 m a.s.l. ), is characterized by lowland humid conditions with bimodal annual rainfall distribution that ranges from 1155 to 1955 mm, mean annual temperature of 29 to 31 °C, and relative humidity that ranges from 69% to 79% (Uguru et al, 2011). Sixteen cucumber genotypes obtained from the National Agricultural Extension, Research and Liaison Services (NAERLS), Ahmadu Bello University, Samaru Zaria, were used for the trial.…”
Section: Methodsmentioning
confidence: 99%
“…This is also reflected by the minimal variation in RH (≈ 2 %) over the period resulting to consistent influence (Table 3). The analysis of the three climatic elements from the same station over 40 years by Uguru et al (2011) also showed that the RH was the most stable element but over past five years (2005)(2006)(2007)(2008)(2009)(2010), average values of the three elements had been on the increase. From Table 3 the trends in their variations were the same for both during the study period and for the long term averages even though that of rainfall was lower while that of the RH was higher.…”
Section: Resultsmentioning
confidence: 99%